Auditoría a los estados financieros de la farmacia Oriental, ubicada en el cantón Shushufindi provincia de Sucumbíos, correspondiente al periodo 2015 - Garcia Loor, Jennifer Carolina (2017)
The present research work determine the reasonableness with which the Financial Statements are presented through the verification and evaluation of The records of the accounting and financial operations carried out in the company; The information obtained will help your proprietary Manager to make decisions that lead to improvement in the management of material and economic resources. In the development of the thesis the objectives were fulfilled, when applying the Audit to the Financial Statements of the "Oriental" Pharmacy, as well as to make the diagnosis of the Financial Statements of the same, through the selection and application of audit evidence And on the basis of this, to obtain sufficient, relevant and competent evidence in order to prepare the final report with the corresponding opinion focused on providing possible solutions that will enable a better accounting and financial organization reflected in the Financial Statements. Among the main conclusions, it is clear that the Oriental Pharmacy does not have a timely control that records daily income, expenditure and contributions that are reported to control agencies such as the Internal Revenue Service and the Ecuadorian Social Security Institute, significantly altering The Balances, in response to this, it is advisable to hire a plant accountant who registers and reports on the accounting facts generated in the company, in order that the Financial Statements present themselves Rasonably.